Identification of candidate flowering and sex genes in white Guinea yam (D. rotundata Poir.) by SuperSAGE transcriptome profiling - Girma Tessema, G.; Natsume, S.; Carluccio, A.V.; Takagi, H.; Matsumura, H.; Uemura, A.; Muranaka, S.; Stavolone, L.; Gedil, Melaku A; Spillane, Charles; Terauchi, R.; Tamiru, M. (Public Library of Science, 2019)
Dioecy (distinct male and female individuals) combined with scarce to non-flowering are common features of cultivated yam (Dioscorea spp.). However, the molecular mechanisms underlying flowering and sex determination in Dioscorea are unknown. We conducted SuperSAGE transcriptome profiling of male, female and monoecious individuals to identify flowering and sex-related genes in white Guinea yam (D. rotundata). SuperSAGE analysis generated a total of 20,236 unique tags, of which 13,901 were represented by a minimum of 10 tags. Of these, 88 tags were significantly differentially expressed in male, female and monoecious plants. Of the 88 differentially expressed SuperSAGE tags, 18 corresponded to genes previously implicated in flower development and sex determination in multiple plant species. We validated the SuperSAGE data with quantitative real-time PCR (qRT-PCR)-based analysis of the expression of four candidate genes. Our findings suggest that mechanisms of flowering and sex determination are likely conserved in Dioscorea. We further investigated the flowering patterns of 1938 D. rotundata accessions representing diverse geographical origins over two years, revealing that over 85% of the accessions are either male or non-flowering, and that less than 15% are female, while monoecious plants are rare. Intensity of flowering appeared to be a function of sex, with male plants flowering more abundantly than female ones. Candidate genes identified in this study can be targeted with the aim to induce regular flowering in poor to non-flowering cultivars. Findings of the study provide important inputs for further studies aiming to overcome the challenge of flowering in yams and to improve the efficiency of yam breeding.